La teoria dell’arte di Flaubert nell’interpretazione di Croce - Paolo D’Angelo (Flaubert: Revue Critique et Génétique)
Benedetto Croce always greatly admired Flaubert’s theories on art, such as they are expressed in his Correspondence. We find numerous traces of this admiration in Croce’s works, from the Estetica (1902) up to his last writings. According to Croce Flaubert embodies the figure of a writer who, while lacking an actual training in philosophy, was capable of conceiving artistic phenomena with greater depth than most theorists of his time. Thus Croce places Flaubert next to Charles Baudelaire or Henri Becque and in opposition to academic critics. For Croce Flaubert belongs to a minority but decisive tradition that in the 20th century was able to elaborate a new vision of the relationship between form and content in art: a tradition to which belong De Sanctis in Italy, Fiedler and Hanslick in Germany. Yet Croce never devoted a specific study to Flaubert’s art theory. After recalling Croce’s appraisal of Flaubert this article will offer a possible explanation for this hiatus.